(untitled) (Research, Society and Development, 2020)
This article introduces reflexive approximations of Paulo Freire’s ideas with the daily concrete of an educational practice of popular nature, represented through narrative profiles from northeastern women educators who lived pedagogies gestated in community frontiers. It comes from a research of qualitative nature which integrated a doctoral project entitled Trajectories of female popular educators in the state of Sergipe-Brazil. From the inter-encounter methodology, inspired by the hermeneutic phenomenology, as an approach method and the Oral History as a procedural method, recollections and experiences of female popular educators compromised with literacy practices in its own communities were analysed. The analytical path reupdated the concept of Popular Education, elevating it beyond the educational dimension and placing it as a piece of knowledge generated by a daily experience. The dialogic evidences have produced a close theoretical translation of the experimental field with the Freirean perspective on adult literacy, oriented as a basic human right and seen as a decisive tool for fighting poverty and the inadequate distribution of life essential resources.